An Application of the Role Play Method in Improving the Social and Emotional Abilities of Children Aged 4-5 Years at PAUD Alqomar - Komariyah, Komariyah; Mahmudah, Masrurotul; Azizah, Isnaini Nur; Dea, Leli Fertiliana; Suhono, Suhono (International Journal on Advanced Science, Education, and Religion, 2024)
Alqomar PAUD Many social and emotional skills of children aged 4 to 5 years are still underdeveloped, so teachers attempt to develop children's social and emotional skills through role-playing methods. The aim of this research is to determine the application of the role-playing method to improve the social and emotional skills of children aged 4-5 years at PAUD Alqomar. This research is field research using qualitative methods. The main data sources are teachers and students. Alkmaar Early Childhood Education Research Site. Currently, inductive methods are used for data analysis. Based on the results of the discussion, it can be concluded that the application of the role-playing method to improve the social and emotional skills of children aged 4-5 years has been achieved well at PAUD Alqomar. The use of role play techniques at PAUD Alqomar has been proven to improve the social and emotional skills of children aged 4 to 5 years. This can be seen from the child's skills before the role-playing method was introduced, but after the role-playing method was introduced, the child's social and emotional skills began to develop. Keywords: Role Play Method, Social Emotional, Social and Emotional Abilities